(untitled) (JPK : Jurnal Proteksi Kesehatan, 2022)
Mangkokan is one of traditional medicinal plants that has many benefits in restoring health, such as preventing hair loss, treating wounds, antibacterial agent, improving blood circulation and as an antioxidant agent. This study aimed to examine the activity of the ethanol extract of the mangkokan leaf (Polyscias scutellarium (Burm.f.) Fosberg) against Escherichia coli and Staphylococcus aureus. The extraction process was carried out by gradual maceration through three solvents including n-hexane, ethyl acetate, and ethanol. The antibacterial activity test was carried out by agar diffusion method by calculating diameter of the inhibition zone from ethanol extract of mangkokan leaf with four variation concentrations: 20%, 40%, 60%, and 80%. The antibacterial activity of the ethanolic extract of the mangkokan leaf against Escherichia coli resulted in the average diameter od the inhibition zone at the following concentrations: 20% (5,9 mm), 40% (5,2 mm), 60% (5,9 mm), dan 80% (7,03 mm. While antibacterial test against Staphylococcus aures resulted in the average diameter of the inhibition zone at the following concentrations: 20% (9,66 mm), 40% (10,71 mm), 60% (11,27 mm), 80% (12,42 mm).